2019
DOI: 10.1177/2331216519845596
|View full text |Cite
|
Sign up to set email alerts
|

Individual Variations in Effort: Assessing Pupillometry for the Hearing Impaired

Abstract: Assessing effort in speech comprehension for hearing-impaired (HI) listeners is important, as effortful processing of speech can limit their hearing rehabilitation. We examined the measure of pupil dilation in its capacity to accommodate the heterogeneity that is present within clinical populations by studying lexical access in users with sensorineural hearing loss, who perceive speech via cochlear implants (CIs). We compared the pupillary responses of 15 experienced CI users and 14 age-matched normal-hearing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
44
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(52 citation statements)
references
References 88 publications
4
44
4
Order By: Relevance
“…Percent change in event-related pupil dilation (ERPD) were then calculated, per each individual trial and participant, according to the formula described in Wagner et al (2019), % change ERPD = 100x (observation -baseline)/baseline. Baseline was defined as the one-second period preceding the onset of the noise (i.e., time 0 in all graphical representations).…”
Section: Pupillometry Data Processingmentioning
confidence: 99%
See 1 more Smart Citation
“…Percent change in event-related pupil dilation (ERPD) were then calculated, per each individual trial and participant, according to the formula described in Wagner et al (2019), % change ERPD = 100x (observation -baseline)/baseline. Baseline was defined as the one-second period preceding the onset of the noise (i.e., time 0 in all graphical representations).…”
Section: Pupillometry Data Processingmentioning
confidence: 99%
“…They further showed that this later-occurring, and longer-lasting “repair” process observed in CI users, could easily be perturbed, and even canceled by later-occurring sounds, especially when these were intelligible utterances ( Winn and Moore, 2018 ). More recently, Wagner et al (2019) reported that CI users showed increased variability in their evoked pupil responses compared to matched normal-hearing participants, suggesting that this variability could be clinically meaningful and could be an index of processing load in individual patients. Even if these first studies highlight the interest of pupillometry to explore cognitive processing involved during listening tasks in CI users, the potential of pupillary responses as a clinical objective tool to evaluate CI performance remains to be explored.…”
Section: Introductionmentioning
confidence: 99%
“…In studies such as these, task-related changes in pupil diameter are typically expressed as a difference from a prestimulus baseline in the form of a brief silent period prior to presentation of the speech stimulus. The pupil size measured in this pre-stimulus window is referred to as the baseline pupil diameter (BPD; Kuchinsky et al, 2013;Koelewijn et al, 2015;Winn and Moore, 2018;Wagner et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…We observed that mean pupil dilation and baseline pupil size generally declined over the course of a block (48 sentences). This decline might reflect task familiarization, but also fatigue (Wagner et al, 2019). Given the role of attention in adapting to noise-vocoded speech (Huyck and Johnsrude, 2012), we expected to see a more sustained baseline pupil size across trials.…”
Section: A Intelligibility and Listening Effortmentioning
confidence: 97%